2015
DOI: 10.1016/j.visres.2015.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Veering in hemi-Parkinson’s disease: Primacy of visual over motor contributions

Abstract: Veering while walking is often reported in individuals with Parkinson’s disease (PD), with potential mechanisms being vision-based (asymmetrical perception of the visual environment) or motoric (asymmetry in stride length between relatively affected and non-affected body side). We examined these competing hypotheses by assessing veering in 13 normal control participants (NC) and 20 non-demented individuals with PD: 9 with left-side onset of motor symptoms (LPD) and 11 with right-side onset (RPD). Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…For example, postural instability in PD has been shown to be greater when visual fixation is impaired. 6 Visual impairment is also associated with physical inactivity, which is itself a risk factor for falls and hip fracture, 42,43 and physical inactivity is also negatively associated with PD-related outcomes. 44 Visual impairment may also increase the risk of hallucinations in PD, [7][8][9][10] and both hallucinations and dementia are risk factors for falls.…”
Section: Discussionmentioning
confidence: 99%
“…For example, postural instability in PD has been shown to be greater when visual fixation is impaired. 6 Visual impairment is also associated with physical inactivity, which is itself a risk factor for falls and hip fracture, 42,43 and physical inactivity is also negatively associated with PD-related outcomes. 44 Visual impairment may also increase the risk of hallucinations in PD, [7][8][9][10] and both hallucinations and dementia are risk factors for falls.…”
Section: Discussionmentioning
confidence: 99%
“…We can speculate that degeneration in the most affected brain side also occurred in perceptual brain areas. Previous studies have also indicated that veering is side affected to PD-dependent [60,61]. Perceptual/sensorial asymmetry is a characteristic in the earliest stages of the disease [54,59,62,63], which seems to be manifested depending on the basal ganglia-cortical loops activated by the visual and motor demands of the task [62].…”
Section: Strategies Of People With Pd To Deal With Asymmetry When Cirmentioning
confidence: 98%
“…Interventions to correct walking abnormalities such as veering in PD should incorporate vision-based strategies rather than solely addressing motor asymmetries, and should be tailored to the distinctive navigational profiles of leftside onset of motor symptoms (LPD) and right-side onset (RPD). [28] The functional organization of the pre-frontal cortex (PFC) has been explored with a considerable evidence for a left hemisphere (LH) "interpreter". Recent investigations have added evidence for several roles of the right PFC in reasoning, problem solving, and decision-making; focusing on the beneficial complementary role of the right PFC in maintaining and enhancing the role of the left PFC, the "interpreter".…”
Section: Functional Asymmetriesmentioning
confidence: 99%